1991
DOI: 10.1093/carcin/12.4.653
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of the potato-derived chymotrypsin inhibitor with C3H/10T1/2 cells

Abstract: Protease inhibitors have been shown to be effective suppressors of carcinogenesis in vitro and in vivo. For example, the potato-derived chymotrypsin inhibitor 1 (CI-1) suppresses radiation transformation of C3H/10T1/2 cells in vitro. In the current study, we have investigated the interaction of CI-1 with C3H/10T1/2 cells. At the concentrations examined, CI-1 was non-toxic and had no effect on the doubling time or saturation density of these cells. This compound was taken up by these cells in a time dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The specificity of the effect of proteasome inhibition was tested by the use of alternative protease inhibitors. Since some of these inhibitors have low cell permeability (Suzuki et al, 1981; Billings et al, 1991; Ishisaka et al, 1998; Taylor et al, 2004), high concentrations were applied in the culture medium of RPE cells for up to 16 h. E64 (10 μM), Leupeptin (50 μM), Pepstatin A (1 μM), Soybean Trypsin inhibitor (100 μM), and Chymotrypsin inhibitor (100 μM) were used. None caused mitotic arrest or the emergence of mitotic cells with multiple MTOCs.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of the effect of proteasome inhibition was tested by the use of alternative protease inhibitors. Since some of these inhibitors have low cell permeability (Suzuki et al, 1981; Billings et al, 1991; Ishisaka et al, 1998; Taylor et al, 2004), high concentrations were applied in the culture medium of RPE cells for up to 16 h. E64 (10 μM), Leupeptin (50 μM), Pepstatin A (1 μM), Soybean Trypsin inhibitor (100 μM), and Chymotrypsin inhibitor (100 μM) were used. None caused mitotic arrest or the emergence of mitotic cells with multiple MTOCs.…”
Section: Resultsmentioning
confidence: 99%
“…The BBI has also been shown to suppress radiation-induced transformation of C3H/1OT/2 mouse embryo fibroblast cells at nanomolar concentrations (21) and to inhibit the transformation of BALB/3T3 cells induced by radiation or chemical carcinogens (benzo[a]pyrene and P-propiolactone) (6). We have shown that BBI as well as other anticarcinogenic protease inhibitors are internalized by C3H/10T1/2 cells (7,28,29).…”
Section: Introductionmentioning
confidence: 85%
“…The BBI has also been shown to suppress radiation-induced transformation of C3H/1OT/2 mouse embryo fibroblast cells at nanomolar concentrations (21) and to inhibit the transformation of BALB/3T3 cells induced by radiation or chemical carcinogens (benzo[a]pyrene and P-propiolactone) (6). We have shown that BBI as well as other anticarcinogenic protease inhibitors are internalized by C3H/10T1/2 cells (7,28,29).A major focus of our research is to elucidate the mechanism(s) by which protease inhibitors such as BBI suppress carcinogenesis. To accomplish this goal, we believe it will be necessary to identify and characterize the target enzymes that specifically interact with the BBI.…”
mentioning
confidence: 99%
“…1) quelled the X-ray-induced transformation of mouse embryo fibroblast cells (Yavelow et al, 1985). Potato protease inhibitors (PPI) I and II showed similar in vitro effects (Billings et al, 1991). Potato carboxypeptidase inhibitor suppressed growth of several human adenocarcinoma cell lines, most probably due to its antagonistic effect on epidermal growth factor expression (Blanco-Aparicio et al, 1998).…”
Section: Cancermentioning
confidence: 99%